PENGEMBANGAN MODEL PEMBELAJARAN BERBASIS FITRAH UNTUK MENINGKATKAN PENDIDIKAN KARAKTER - Marwa, Najla Kamilia; Supriadi, Udin; Firmansyah, Mokh. Iman (Prodi PAI STIT Sunan Giri Bima, 2023)
Character education is an approach that aims to shape individual character to have good attitudes, behavior, and morality. This is in line with human nature which has an important role in shaping one's character. In education, nature-based learning models can be a strong foundation for implementing character education. The dynamic and complex developments of the times affect one's character. Therefore the development of human character by nature is becoming increasingly important. Humans need to understand and respect fitrah as the basis for living life and facing the various challenges they face. By combining nature-based character education, humans can build strong characters, have integrity, and have high moral resilience in facing the ever-evolving changing times. This study aims to develop a nature-based learning model to improve character education. The method used is library research or library research where the data is taken from trusted journals. The result that I got is the development of a nature-based learning model to improve character education which has several strategic steps to make it happen.